Efficacy and safety of Wuling capsule for the treatment of mild depression in patients with early Parkinson’s disease in China: a randomized clinical trial - Yuwen Zhao; Lin Li; Dongya Huang; Wentao Li; Qiuyan Zhao; Huiqin Liu; Ran Xiong; Meijuan Liu; Jing Gan; Na Wu; Zhihua Liu; Xinxin Chen; et al. (BMC Complementary Medicine and Therapies)
Abstract Background Depression is a prevalent non-motor symptom of Parkinson’s disease (PD) that significantly impacts patients’ quality of life. The Wuling capsule, a traditional Chinese medicine, is often utilized for treating depression, and this herbal medicine has been used to treat those PD patients with depression. This study aims to assess the efficacy and safety of Wuling capsule in treating mild depression in patients with early PD. Methods This multicenter, double-blind, placebo-controlled randomized clinical trial included 160 patients with early PD who presented with a Hamilton Rating Scale for Depression (HAMD) score between 8 and 17 at the time of admission. The trial was conducted across five hospitals in China from December 2021 to March 2024. Eligible patients were randomly assigned to receive either Wuling capsule (0.99 g orally three times daily) or a placebo (0.99 g orally three times daily) for a duration of 12 weeks. Additional treatment according to established clinical guidelines.The primary outcome measure was the change in HAMD score. All statistical analyses were conducted on an intention-to-treat population. Results After 12 weeks of treatment, among the 160 patients with early PD and depression, 80 were assigned to the Wuling capsule group and 80 to the placebo group, with the median age of 70.5 (IQR,67.00–75.00) years and 77 (48.13%) were male. Patients in the Wuling capsule group demonstrated significantly greater reductions in depression severity compared to the placebo group at multiple time points: week 4 (difference, − 1.21 [95% CI, -2.38 to -0.04; P = 0.042]), week 8 (difference, − 1.41 [95% CI, -2.81 to -0.02; P = 0.047]), and week 12 (difference, − 1.46 [95% CI, -2.89 to -0.04; P = 0.044]). Adverse events were reported in 3 of 80 patients (3.75%) in the Wuling capsule group and 3 of 80 patients (3.75%) in the control group (P = 1), indicating no significant difference. Conclusion This randomized clinical trial demonstrated that treatment with Wuling capsule over a 12-week period effectively reduced HAMD score in patients with mild depression associated with PD and the treatment was well tolerated. Trial registration Chinese Clinical Trial Registry; registration number: ChiCTR2100046195; prospectively registered on May 9th, 2021.